PEMBINAAN MOTIVASI PRESTASI GURU MELALUI SUPERVISI PEMBELAJARAN - Nurhadi (JOEL: Journal of Educational and Language Research, 2022)
In this article discusses the Guidance of Teacher Achievement Motivation. Analysis of literacy studies used to find solutions how efforts to build teacher achievement motivation to improve the quality of education, equipped with a discussion to complete the conclusion. Is one of the tasks of the principal. The principal must provide guidance to teachers in an effort to improve the quality of education. Conclusions: (1) Teacher Achievement is a series of efforts conducted by school principals, supervisors, supervisors and other supervisors of teachers with the aim of promoting and improving the quality of work of educators which impact on improving the quality of education. (2) The factors that influence the teacher's achievement motivation from within the teacher itself and from the outside environment and (3) The Formation of Achievement Motivation Achievement is: giving opportunity to improve career, giving sense of safety and comfort, giving appreciation, harmonious relationship